2020
DOI: 10.1371/journal.pone.0239397
|View full text |Cite
|
Sign up to set email alerts
|

Human-animal relationships and interactions during the Covid-19 lockdown phase in the UK: Investigating links with mental health and loneliness

Abstract: Background The Covid-19 pandemic raises questions about the role that relationships and interactions between humans and animals play in the context of widespread social distancing and isolation measures. We aimed to investigate links between mental health and loneliness, companion animal ownership, the human-animal bond, and human-animal interactions; and to explore animal owners' perceptions related to the role of their animals during lockdown. Methods A cross-sectional online survey of UK residents over 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
205
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(231 citation statements)
references
References 39 publications
18
205
6
2
Order By: Relevance
“…Somewhat paradoxically, given the results of this study, suggested strategies to mitigate the negative effects of lockdown restrictions have highlighted the beneficial effects of exercise, and proposals including walking with a dog have been cited [ 46 ]. The reductions in dog walking frequency and duration during the lockdown period reported by owners in our study support the results of a recent study which indicated that 21.7% of UK companion animal owners, surveyed between 16 April and 31 May 2020, were worried about their animal(s) because of COVID-19 restrictions to exercise/walks [ 47 ]. Hence, owners’ concerns about the welfare of their dogs is an important factor that should not be overlooked.…”
Section: Discussionsupporting
confidence: 89%
“…Somewhat paradoxically, given the results of this study, suggested strategies to mitigate the negative effects of lockdown restrictions have highlighted the beneficial effects of exercise, and proposals including walking with a dog have been cited [ 46 ]. The reductions in dog walking frequency and duration during the lockdown period reported by owners in our study support the results of a recent study which indicated that 21.7% of UK companion animal owners, surveyed between 16 April and 31 May 2020, were worried about their animal(s) because of COVID-19 restrictions to exercise/walks [ 47 ]. Hence, owners’ concerns about the welfare of their dogs is an important factor that should not be overlooked.…”
Section: Discussionsupporting
confidence: 89%
“…Having a canine companion also appears to have had a protective impact on mental and physical health through added daily structure and exercise. A recent study that assessed the role between companion animals and their humans during Covid-19, found that companion animal ownership was related to better mental health scores [ 41 ]. In the current study, spending time with their dog appeared to greatly diminish participants’ sense of isolation and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Companion animals provide emotional support and prevent loneliness [ 22 ], and they become even more vital in times where social distancing and social isolation prevents regular interaction with other people. Indeed, pet ownership itself was considered more influential to combat loneliness than the strength of the human-animal bond [ 23 ]. Here equestrian facility owners may have an advantage as in spite of the anxiety that the pandemic is causing, they are still able to access their horses and perhaps even spend more time with them than previously.…”
Section: Discussionmentioning
confidence: 99%